The Association between a Polygenic Alzheimer Score and Cortical Thickness in Clinically Normal Subjects - Sabuncu, Mert R.; Buckner, Randy L.; Smoller, Jordan W.; Lee, Phil Hyoun; Fischl, Bruce; Sperling, Reisa A. (Cerebral cortex (New York, N.Y. 1991), 2012)
Late-onset Alzheimer's disease (AD) is 50-70% heritable with complex genetic underpinnings. In addition to Apoliprotein E (APOE) ε4, the major genetic risk factor, recent genome-wide association studies (GWAS) have identified a growing list of sequence variations associated with the disease. Building on a prior large-scale AD GWAS, we used a recently developed analytic method to compute a polygenic score that involves up to 26 independent common sequence variants and is associated with AD dementia, above and beyond APOE. We then examined the associations between the polygenic score and the magnetic resonance imaging-derived thickness measurements across AD-vulnerable cortex in clinically normal (CN) human subjects (N = 104). AD-specific cortical thickness was correlated with the polygenic risk score, even after controlling for APOE genotype and cerebrospinal fluid (CSF) levels of β-amyloid (Aβ(1-42)). Furthermore, the association remained significant in CN subjects with levels of CSF Aβ(1-)(42) in the normal range and in APOE ε3 homozygotes. The observation that genetic risk variants are associated with thickness across AD-vulnerable regions of interest in CN older individuals, suggests that the combination of polygenic risk profile, neuroimaging, and CSF biomarkers may hold synergistic potential to aid in the prediction of future cognitive decline.